Instituições participativas e políticas públicas: uma nova literatura para a agenda de pesquisa - Brasil, Felipe Gonçalves (Universidade Federal de São Carlos, 2013)
Starting with the organization of social movements in the late 1960s, crossing the institutionalization of participation in the 1988 Constitution and disemboguing on the recent analysis on the institutional engineering of Participatory Budgeting from the 2000s, the research agenda on participatory institutions in Brazil, not only consolidated on the academic setting as well as is growing and diversifying in the last decades. Aiming to insert the most recent literature of the field of public policy in the studies in of participatory institutions, this dissertation is the union of two major movements: The first intends to redeem the theories of political science that guided the studies strongly about these new centers of popular empowerment. Based on the theories democratic and on the neo-institutionalism, the national literature produced extensive and important material about the extra-parliamentary representation and about the reconfiguration of the relationship between state and society, but also on the effects of institutionalization of participation and about their history and evaluation of its effectiveness. After reviewing the literature and what was produced from it, the second movement advocates the public policies as an epistemological field. Border to the field of political science, is through the explanation of some of his own theories and models of analysis of policy that aims to show new horizons for research agenda about the participatory institutions. Under the assumption that the participatory politics institutionalized in the 1988 Constitution can be understood as public policies, this work aims to show how, integrated, political science theories and models of public policy analysis can produce issues that drive to build a new research agenda of participatory institutions in Brazil.
Keywords: Ciência política; Políticas públicas; Formulação de políticas; Participação política; Institucionalização Instituições participativas; Democracia participativa; Teorias da democracia; Modelos de análise de políticas públicas; Public Policy; Participatoryinstitutions; Participatory democracy; Theories of democracy; Models of policy analysis; CIENCIAS HUMANAS::CIENCIA POLITICA